The role of the heutagogy approach in advanced adult education as rebuilding the vocational self-concept in the industrial era 4.0 and society 5.0 - Titi Sumarni; Putu Sudira (Jurnal Pendidikan Vokasi, 2022)
Technical and Vocational Education and Training (TVET) is established by UNESCO and ILO as education and training beneficial for the community. The community will be able to develop when they can use their leadership skill properly. This is what makes adult vocational education very important in building the nation. One example of the role of adult vocational education is reducing unemployment through a heutagogy approach. The heutagogy approach centered on individual participants, where the individual has full autonomy in creating their learning. The heutagogy approach is also helpful for developing an individual's self-capacity and vocational self-concept. The individual vocational self-concept through the heutagogy approach can help students, graduates, alumni, and the community develop skills (re-skills, up-skills) and prepare to enter the world of work. The skill development can be done by forming (re-establishing) the individual's vocational self-concept. In the development of the industrial revolution 4.0 and society 5.0, the role of self-concept with a heutagogy approach in advanced adult education is to build vocational self-concepts so that they can be independent in learning, prepare work skills and utilize technology well as lifelong learning, and make an individual as a digital transformation society. Besides that, the heutagogy approach has a triple-loop learning process that aims to make the right decision on the learning power of vocational self-concept. With the preparation of work skills, the self-concept of vocational maturity means that the higher the self-concept, the higher the maturity in the industrial era 4.0 career and Society 5.0 or with the existence of vocational self-concept in the future can make mature decisions.